TERAPIAS MENTE-CUERPO: UNA REINTEGRACIÓN DE MENTE, CUERPO Y ESPÍRITU - Rodríguez Barquero, Vivian (2005)
The purpose of this article is to analize the   existing information about mind-body medicine, its development like teorical- metodological bases, its    health conception and its vision of the human body.    Beside, it will focus in two body-therapies, practicing in Costa Rica: Feldenkrais and "Corporal Expression". In order to obtain a better view of    the possible benefits and challenges of the body-    health conception.